N-Heterocyclic carbenes and their precursors in functionalised porous materials. (16th November 2021) - Wang, Yao; Chang, Jin-Ping; Xu, Rui; Bai, Sha; Wang, Dong; Yang, Guo-Ping; Sun, Li-Ying; Li, Peng; Han, Ying-Feng
Abstract : Recent progress on the synthetic methods, structural features, and promising applications of NHCs and their precursors in functionalised porous materials is summarised. Abstract : Though N-heterocyclic carbenes (NHCs) have emerged as diverse and powerful discrete functional molecules in pharmaceutics, nanotechnology, and catalysis over decades, the heterogenization of NHCs and their precursors for broader applications in porous materials, like metal–organic frameworks (MOFs), porous coordination polymers (PCPs), covalent-organic frameworks (COFs), porous organic polymers (POPs), and porous organometallic cages (POMCs) was not extensively studied until the last ten years. By de novo or post-synthetic modification (PSM) methods, myriads of NHCs and their precursors containing building blocks were designed and integrated into MOFs, PCPs, COFs, POPs and POMCs to form various structures and porosities. Functionalisation with NHCs and their precursors significantly expands the scope of the potential applications of porous materials by tuning the pore surface chemical/physical properties, providing active sites for binding guest molecules and substrates and realizing recyclability. In this review, we summarise and discuss the recent progress on the synthetic methods, structural features, and promising applications of NHCs and their precursors in functionalised porous materials. At the end, a brief perspective on the encouraging future prospects and challenges in this contemporary field is presented. This review will serve as a guide for researchers to design and synthesize more novel porous materials functionalised with NHCs and their precursors.